Implementasi Konsep Responsible Tourism Marketing (RTM) di Desa Wisata Jatimulyo Kabupaten Kulonprogo Yogyakarta - Roels Ni Made Sri Puspa Dewi (Media Wisata, 2020)
Jatimulyo Tourism Village has many natural tourism objects, cultural and is supported by local culinary. The existence of many attractions presents a new problem in the form of competition between attractions that bring tourists as much as possible without regard to the carrying capacity of the environment. The research objective is to identify the marketing plan consisting of marketing mix analysis (7P), STP and the implementation of Responsible Tourism Marketing (RTM). The method of collecting data uses direct observation, interviews and documentation. Determination of the sample using Snowball Sampling with 20 people sampling consisting of managers of tourist attractions and some local community who work on these attractions. Data analysis uses interactive models, namely: data collection, data reduction, data display and drawing conclusions. The results showed that tourism products owned by Jatimulyo Tourism Village strongly support the implementation of the RTM. Tourism activities such as cave trekking, learning local culinary, swimming in waterfalls, take some photos and exploring the village. The application of RTM is a solution to deal with competition between attractions because they have to pay attention to the carrying capacity and nature conservation